The Effect of Social Media Marketing and Brand Awareness on Purchase Decisions through Purchase Intention in Kopiria - Edo Dermawan; Arwin Sanjaya; Tuti Wediawati (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of social media marketing and brand awareness to purchase decisions through purchase intention. The type of research used is explanatory research using a quantitative approach. The sample used is 100 respondents who are consumers of Kopiria Kartini Samarinda using a non-probability sample with purposive sampling technique. Analysis of the data used is path analysis. The results showed that the Social Media Marketing variable had a significant influence to the Purchase Intention variable, the Brand Awareness variable had a significant influence to the Purchase Intention variable, the Purchase Intention variable had a significant influence to the Purchase Decision variable, the Social Media Marketing variable didn’t have a significant to the Purchase Decision variable, the Brand Awareness variable didn’t have a significant effect to the Purchase Decision variable, the Social Media Marketing variable through Purchase Intention as the intervening variable has a significant influence to the Purchase Decision variable, and the Brand Awareness variable through Purchase Intention as the intervening variable has a significant influence to the Purchase Decision variable. Thus Kopiria Kartini Samarinda continues to strive to carry out marketing strategies that keep up with the times. This will make consumer interest in the brand will always increase and lead to purchasing decisions.